(untitled) (Jurnal Online Pertanian Tropik, 2019)
Apple velvet (Diospyros blancoi) is one of the local fruits which classified as a rare plant even it has high economic value. Apple velvet has various morphology that needs selection from any various characters to identify the most superior character and has high potential to be developed. The analysis of diversity from one population can be identified to know the morphology character from the plant. The commonly used characteristics include tree trunks, leaves, flowers, fruits, and seeds. This study was conducted using the quantitative and qualitative methods the result of the characterized plants showed that the apple velvet plants in Germplasm Collection Garden of Lipi Cibinong have the average height between 3.5-15 m, stem diameter between 14.1-72.29 cm has no shapes of leaves such as oval and wide oval. White flower crown, 2 shapes of fruits such as round and oval pattern, 2 shapes of seeds such as elliptic and biconvex. Keywords: apple velvet plants, characterization, rare plant